Development of hybrid electrospun alginate-pulverized moringa composites - Orisawayi, Abimbola Oluwatayo; Koziol, Krzysztof K.; Hao, Shuai; Tiwari, Shivam; Rahatekar, Sameer S. (Royal Society of Chemistry, 2024)
The consideration of biopolymers with natural products offers promising and effective materials with intrinsic and extrinsic properties that are utilized in several applications. Electrospinning is a method known for its unique and efficient performance in developing polymer-based nanofibers with tunable and diverse properties presented as good surface area, morphology, porosity, and fiber diameters during fabrication. In this work, we have developed an electrospun sodium alginate (SA) incorporated with pulverized Moringa oleifera seed powder (PMO) as a potential natural biosorbent material for water treatment applications. The developed fibers when observed using a scanning electron microscope (SEM), presented pure sodium alginate with smooth fiber (SAF) characteristics of an average diameter of about 515.09 nm (±114.33). Addition of pulverized Moringa oleifera at 0.5%, 2%, 4%, 6%, and 8% (w/w) reduces the fiber diameter to an average of about 240 nm with a few spindle-like pulverized Moringa oleifera particles beads of 300 nm (±77.97) 0.5% particle size and 110 nm (±32.19) with the clear observation of rougher spindle-like pulverized Moringa oleifera particle beads of 680 nm (±131.77) at 8% of alginate/Moringa oleifera fiber (AMF). The results from the rheology presented characteristic shear-thinning or pseudoplastic behaviour with a decline in viscosity, with characteristic behaviour as the shear rate increases, indicative of an ideal polymer solution suitable for the spinning process. Fourier transform infrared spectroscopy (FT-IR) shows the presence of amine and amide functional groups are prevalent on the alginate-impregnated moringa with water stability nanofibers and thermogravimetric analysis (TGA) with change in degradation properties in a clear indication and successful incorporation of the Moringa oleifera in the electrospun fiber. The key findings from this study position nanofibers as sustainable composites fiber for potential applications in water treatment, especifically heavy metal adsorption.